Engineering materials 2 : an introduction to microstructures and processing - Ashby, M. F.; Jones, David R. H. (David Rayner Hunkin), 1945- (Oxford, England : Butterworth-Heinemann, 2013)
This is a textbook for more advanced students of materials science and mechanical engineering, and is the follow-up to its companion text, Engineering Materials 1: An Introduction to Properties, Applications & Design. This book develops a detailed understanding of the fundamental properties of engineering materials, how they are controlled by processing, formed, joined and finished, and how all of these factors influence the selection and design of materials in real-world engineering applications. Each chapter is designed to cover the content of one 50-minute lecture. Includes case studies, worked examples, homework problems, updated illustrations, and numerous detailed case studies throughout. It allows students to see the practical applications of the material just presented in their lecture. Online support materials include a set of interactive materials science tutorials, allowing students to test their knowledge of materials science in an interactive way.
Includes bibliographical references (p. 541-542) and index.
Buku bacaan asas fakulti.
Keywords: Materials -- Textbooks; Materials science